Tindak Tutur Ilokusi pada Film Tak Kemal Maka Tak Sayang Karya Fajar Bustomi - Siti Nadiroh; Ida Puspita Rini; Deacy Eka Pratiwi; Istianah Istianah (Universitas Palangka Raya, 2022)
Illocutionary speech acts can be found in everyday life or can also be found in movies which are a reflection of life. The author focuses research questions on (1) directive illocutionary speech acts; and (2) expressive illocutionary speech acts. This research method is descriptive qualitative. This method is used because the author describes the results of the analysis by describing. After conducting the analysis, the writer concludes that directive illocutionary speech acts and expressive illocutionary speech acts found in the dialogue of the film are based on several factors that support the validity of directive illocutionary speech acts and expressive illocutionary speech acts in the dialogue, namely the existence of other meanings from the actors' utterances. as well as the influence that arises from the speaker to the interlocutor.